Association between hemoglobin glycation index and non-alcoholic fatty liver disease - Xing, Yuling; Zhen, Yunfeng; Yang, Liqun; Huo, Lijing; Ma, Huijuan (Frontiers in Endocrinology, 2023)
Objective: Hemoglobin glycation index (HGI) can reflect the biological variability of hemoglobin A1c (HbA1c). However, limited studies existed on the relationship between HGI and non-alcoholic fatty liver disease (NAFLD).This study aimed to further explore the relationship between HGI and NAFLD.It was expected to provide new ideas for the early identification of patients with a high risk of NAFLD. Methods: The present study was a retrospective study using physical examination data from Japan. Participants were divided into quartiles (Q1–Q4) based on the level of HGI，and the lowest quartile (Q1) was used as the reference group. The study subjects were divided into two subgroups on the basis of whether they were complicated with NAFLD： NAFLD group and non-NAFLD group. And baseline characteristics were compared between the groups. Multivariate logistic regression analysis was used to investigate the association of HGI with NAFLD. Mediation analysis was performed to examine the mediation relationship between HGI and NAFLD.In addition, to further verify the reliability of the results, subgroup analyses were performed. Results: Compared to those in the non-NAFLD group, subjects in the NAFLD group reported higher levels of HGI among 14280 subjects. As HGI rose, so did the risk of NAFLD. After adjusting for confounding factors, multivariate logistic regression analysis revealed that HGI was strongly positively related to the prevalence of NAFLD.Mediation analysis indicated that BMI partly mediated the indirect impact of HGI on NAFLD preference. Subgroup analyses were carried out according to age, sex, smoking, waist circumference (WC). Our results indicated that HGI correlated more significantly with NAFLD in subjects who had one of the following motivations, age≤60 years, BMI＞28kg/m2, females，smoking，or abdominal obesity. Conclusions: HGI was an independent risk factor for NAFLD and BMI partly mediated the association between HGI and NAFLD.